Noninvasive rejuvenation strategy of nickel-rich layered positive electrode for Li-ion battery through magneto-electrochemical synergistic activation - Haochen Gong; Yu Cao; Baoshan Zhang; Jinsong Zhang; Yiming Zhang; Huili Wang; Shaojie Zhang; Xiaoyi Wang; Yue Mao; Shuo Liu; Chengyu Han; Qianxin Xiang; et al. (Nature Communications)
Abstract Nickel-rich layered oxides are one of the most promising positive electrode active materials for high-energy Li-ion batteries. Unfortunately, the practical performance is inevitably circumscribed by the structural deterioration deriving from the Ni/Li antisite disorder, leading to severe capacity loss and life attenuation. Herein, we propose an economical and facile rejuvenation strategy by employing the magneto-electrochemical synergistic activation targeting the positive electrode in assembled Li-ion batteries. This approach induces a transition of Ni3+ from high-spin to low-spin, reducing the super-exchange interaction of Ni-O-transition metal (TM). Meanwhile, electrochemical reaction drives Li+ from the host material and promotes Ni3+ to reoccupy TM layer, recovering intrinsic Li site and extending cycle life. The strategy demonstrates that low-quality positive electrodes can be converted to high-quality ones. Notably, the method can revitalize an aged Li-ion pouch cell (SiC||NCM811, 8 Ah nominal capacity) via optimizing cation occupancy and increase its capacity by 10% from 6.49 to 7.14 Ah at 1 C, illustrating the benefits of the upcycling process.